2020
DOI: 10.9734/cjast/2020/v39i130479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Fertilization of Boron, Zinc and Iron on Fruit Quality and Leaf Nutrients Content of Peach cv. Shan-e-Punjab

Abstract: Aims: To study the effect of different micronutrients and number of foliar spray on fruit quality and leaf nutrient content of peach. Study Design: The experiment comprised of seven treatments and conducted on seven years old plants in Randomized Block Design with three replications. Place and Duration of Study: The experiment was conducted at the experimental orchard of Department of Horticulture, CCS Haryana Agricultural University, Hisar during the year 2018. Methodology: The treatments in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Foliar application of micronutrients could be a better alternative to soil application, since the application of these nutrients to soil may be beyond reach to the deep root system of orchards trees (Ziogas et al 2020, Bibi et al 2019, Ahmad et al 2018and Hipps and Davies, 2001. Additionally, the foliar application is more valuable because of quick reaction, recovery of nutrient deficiency (Muradi andGodara, 2020 andSamant et al 2008) and its effectiveness because of boron, manganese (Mn), copper (Cu), Fe and zinc (Zn). However, some indigenous studies have suggested the recommended dose and time of foliar application of micronutrients.…”
Section: Soil Characterisationmentioning
confidence: 99%
“…Foliar application of micronutrients could be a better alternative to soil application, since the application of these nutrients to soil may be beyond reach to the deep root system of orchards trees (Ziogas et al 2020, Bibi et al 2019, Ahmad et al 2018and Hipps and Davies, 2001. Additionally, the foliar application is more valuable because of quick reaction, recovery of nutrient deficiency (Muradi andGodara, 2020 andSamant et al 2008) and its effectiveness because of boron, manganese (Mn), copper (Cu), Fe and zinc (Zn). However, some indigenous studies have suggested the recommended dose and time of foliar application of micronutrients.…”
Section: Soil Characterisationmentioning
confidence: 99%